Attitude Determinant in Entrepreneurship Behavior of Vocational Students’ Entrepreneurship Intention - Ludi Wishnu Wardana; Chamdan Purnama; Saiful Anam; Farij Ibadil Maula (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2020)
This study aim to finding the correlation between emotional intelligence, entrepreneurship self-efficacy, entrepreneurship behavioral attitude, and entrepreneurship intention vocational school students. The data were analyzed using the SEM Smart PLS technique. The study revealed that there is a cause and effect correlation between emotional intelligence and entrepreneurship self-efficacy, entrepreneurship behavioral attitude toward entrepreneurship intention on vocational students in Mojokerto regency as described below: 1) empirically, emotional intelligence was proven to have no direct influence on entrepreneurship intention. However, it has a direct and strong influence on entrepreneurship behavioral attitude, 2) entrepreneurship self-efficacy has direct and strong influence on entrepreneurship behavioral attitude and entrepreneurship intention, and entrepreneurship self-efficacy also has indirect influence on the entrepreneurship intention through entrepreneurship behavioral attitude, 3) entrepreneurship behavioral attitude has direct and strong influence toward entrepreneurship intention.